Water and gender: a decolonial look at hydrosocial transformations in Vila Ideal - THAÍS ZIMOVSKI GARCIA DE OLIVEIRA; RAFAEL FREIRE; GABRIEL FARIAS ALVES CORREIA; ALEXANDRE DE PÁDUA CARRIERI (Cadernos EBAPE.BR)
Abstract The relationship between women and water has gained increasing recognition in recent years. This is evident in the role of water in domestic activities, the water collection performed by women, and the cultural dimensions where attributes such as fluidity, instability, and sensuality are established, aiming at the colonization of both. Simultaneously, the female view has become more prominent in water management, as they are often the ones addressing the issues arising from inadequate access to water and sanitation. This paper examines the case of Vila Ideal, a favela on the outskirts of Belo Horizonte, where residents initially had to walk daily to collect water and have witnessed various territorial transformations. We explore the experiences of Black women who have lived in Vila Ideal since its inception, employing a historical perspective through qualitative research. Using a decolonial framework informed by feminist scholars such as Lélia Gonzalez and Gayatri Spivak, we analyze how water and gender intersect and influence human activities over time, forming what we term hydrosocial relationships of gender.